Literatur Review : Pengaruh Media Pembelajaran Audiovisual terhadap Hasil Belajar Siswa - Az Zahra, Nurul Izza; Fitri, Rahmadhani (Lembaga Yasin AlSys, 2023)
In Education there is a learning process in which the teacher provides the subject matter being taught. However, there are still many teachers who have difficulty conveying material due to limited teaching aids/teaching media. Therefore, there are still many students who have difficulty understanding the material which has an impact on their learning outcomes. Especially in Biology learning that studies living things. Biology lessons are difficult to understand just by reading books, so technological assistance is needed. The data collected shows the need for learning media so that it can help the biology learning process so that students more easily learn and understand biology material so as to improve student learning outcomes. The purpose of this study was to determine the effect of applying audiovisual learning media on learning outcomes in high school students' Biology material. This article uses the literature review method where the author reviews 5 similar articles by comparing pretest and posttest scores in the experimental class about the effect of audiovisual learning media on students' understanding of SINTA indexed biology material. Articles that have been reviewed are obtained through a data base in the form of Google Scholar. The results of the study show that audiovisual learning media influences the learning process in improving high school student learning outcomes in Biology material.